2012
DOI: 10.1371/journal.pone.0040432
|View full text |Cite
|
Sign up to set email alerts
|

Breed-Dependent Transcriptional Regulation of 5′-Untranslated GR (NR3C1) Exon 1 mRNA Variants in the Liver of Newborn Piglets

Abstract: Glucocorticoids are vital for life and regulate an array of physiological functions by binding to the ubiquitously expressed glucocorticoid receptor (GR, also known as NR3C1). Previous studies demonstrate striking breed differences in plasma cortisol levels in pigs. However, investigation into the breed-dependent GR transcriptional regulation is hampered by lacking porcine GR promoter information. In this study, we sequenced 5.3 kb upstream of the translation start codon of the porcine GR gene, and identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 44 publications
2
25
1
Order By: Relevance
“…However, we observed a positive correlation between serum cortisol level and the relative hippocampal weight in neonatal piglets. EHL piglets, which had two-folds higher serum cortisol level (Zou et al, 2012), demonstrated significantly higher hippocampus weight relative to BW as compared with LW piglets. It is noted that the higher serum cortisol level in EHL pigs is a breed characteristic that is evolved over generations of domestication and selection for this breed.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…However, we observed a positive correlation between serum cortisol level and the relative hippocampal weight in neonatal piglets. EHL piglets, which had two-folds higher serum cortisol level (Zou et al, 2012), demonstrated significantly higher hippocampus weight relative to BW as compared with LW piglets. It is noted that the higher serum cortisol level in EHL pigs is a breed characteristic that is evolved over generations of domestication and selection for this breed.…”
Section: Discussionmentioning
confidence: 92%
“…GR is expressed in a tissue-specific manner with multiple GR exon 1 mRNA variants in human (Turner et al, 2006), rodents (Yau et al, 2004) and pigs (Zou et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations